Dynamic demographic analysis - Schoen,Robert (The Springer series on demographic methods and population analysis, 2016)
This volume presents state of the art analyses from scholars dealing with a range of demographic topics of current concern, including longevity, mortality and morbidity, migration, and how population composition impacts intergenerational transfer schemes.